Genome-wide association study of vitamin B6, vitamin B12, folate, and homocysteine blood concentrations - Tanaka, Toshiko; Scheet, Paul; Giusti, Betti; Bandinelli, Stefania; Piras, Maria Grazia; Usala, Gianluca; Lai, Sandra; Mulas, Antonella; Corsi, Anna Maria; Vestrini, Anna; Sofi, Francesco; Gori, Anna Maria; et al. (American journal of human genetics, 2009)
The B vitamins are components of one-carbon metabolism (OCM) that contribute to DNA synthesis and methylation. Homocysteine, a by-product of OCM, has been associated with coronary heart disease, stroke and neurological disease. To investigate genetic factors that affect circulating vitamin B6, vitamin B12, folate and homocysteine, a genome-wide association analysis was conducted in the InCHIANTI (N = 1175), SardiNIA (N = 1115), and BLSA (N = 640) studies. The top loci were replicated in an independent sample of 687 participants in the Progetto Nutrizione study. Polymorphisms in the ALPL gene (rs4654748, p = 8.30 x 10(-18)) were associated with vitamin B6 and FUT2 (rs602662, [corrected] p = 2.83 x 10(-20)) with vitamin B12 serum levels. The association of MTHFR, a gene consistently associated with homocysteine, was confirmed in this meta-analysis. The ALPL gene likely influences the catabolism of vitamin B6 while FUT2 interferes with absorption of vitamin B12. These findings highlight mechanisms that affect vitamin B6, vitamin B12 and homocysteine serum levels.